Therapist effects on outcome and alliance in inpatient psychotherapy: the contribution of patients’ symptom severity - Dinger, Ulrike (Psychotherapy, 2017)
Therapists differ in their effectiveness regarding their patients’ symptomatic improvement as well as their therapeutic alliances, but little is known about influencing factors. The current study aimed to investigate therapist effects on outcome and alliance in inpatient psychotherapy and to estimate the influence of patient severity on the magnitude of therapist effects in this specific setting. We examined differences between individual psychotherapists in their patients’ early alliance and outcome at discharge in a psychotherapy setting of a psychiatric hospital. The sample included 33 therapists and 3,051 patients, and minimum caseload was 30 patients. Outcome was measured as patient-rated symptoms and interpersonal problems as well as therapist-rated impairment. Similarly, alliance was assessed from the patients’ and the therapists’ perspective. First, we estimated the amount of variance that was owing to therapists for patients with average symptom severity. Next, we examined whether the therapist effect was influenced by initial patient severity. Therapist effects on patient-rated symptomatic outcome and alliance were not significantly different from zero. Therapist differences were considerably larger for therapist-rated measures. Patient severity did not significantly influence the therapist effect for patient-rated outcome or alliance. However, there was a u-shaped association for therapist-rated severity and the therapist effect in therapist-rated alliance. Here, therapist differences were larger for patients with either very low or very high initial severity. The magnitude of the therapist outcome effect was smaller in inpatient therapy compared with outpatient settings. (PsycINFO Database Record (c) 2017 APA, all rights reserved)
Gesehen am 20.06.2018